9x-y-3=0

Simple and best practice solution for 9x-y-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-y-3=0 equation:


Simplifying
9x + -1y + -3 = 0

Reorder the terms:
-3 + 9x + -1y = 0

Solving
-3 + 9x + -1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 9x + 3 + -1y = 0 + 3

Reorder the terms:
-3 + 3 + 9x + -1y = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 9x + -1y = 0 + 3
9x + -1y = 0 + 3

Combine like terms: 0 + 3 = 3
9x + -1y = 3

Add 'y' to each side of the equation.
9x + -1y + y = 3 + y

Combine like terms: -1y + y = 0
9x + 0 = 3 + y
9x = 3 + y

Divide each side by '9'.
x = 0.3333333333 + 0.1111111111y

Simplifying
x = 0.3333333333 + 0.1111111111y

See similar equations:

| 3a-15=42 | | -16m^2+25=0 | | f(6)=36+1.531 | | f(6)=36+.1531 | | 2n+6=17 | | y=sw-st^3 | | y=4-3*-5 | | y=-20+10 | | 14+-3p=-20 | | 9p^2=747 | | (x+2)(x-3)=(x+9)(x-4) | | 0=-16t+38.8+3 | | (x+10)= | | 69-3x=7x-19 | | y=-8+8 | | x^2-7=44 | | 4-5u+12+16u=6u-18 | | 5e^4x-6=13 | | 214-5x=40x+24 | | 5x+101=9x-7 | | 15a+15=75 | | 6x-2-8=0 | | 2t(t+2)=1 | | P=b+a | | 6x+2x+3=360 | | x^2-3=33 | | 3x+9=5(2x-7)+3x | | 201-5x=31x+17 | | k^2+10=35 | | 15p=35 | | -4x^2=-4 | | y-2=-1(x+2) |

Equations solver categories